Developing students' reading comprehension using effective reading strategies: a review of previous studies - M. Ali, Aziza; Gupta, Sonia Dutta (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
With the overwhelming number of research studies which focus on examining the different types of reading strategies, it is concerning to note that there are a very little research studies aimed at comparing and contrasting the implementation of the different types of reading strategies in different online and offline contexts. The authors of this literature review examine some previous research studies which focused on the use of different types of reading strategies. The purpose of the literature review is to determine and identify commonly used types of reading strategies which helps in enhancing students’ reading comprehension. The review paper focuses on four types of reading strategies which are metacognitive strategies, cognitive strategies, three phase approach strategies (pre, while, post reading strategies) and support strategies. The reviewed literature indicated that the reading strategies which have been used in reading comprehension are effective for both genders, though, there is some individual preferences between males and females. The authors also compared and contrasted between the research studies to highlight the most effective types of reading strategies which have been used in different contexts. The result provides in-depth details regarding the most effective types of reading strategies which can be implemented in the classroom to enhance the students’ reading comprehension.